Environments conducive to Theobroma cacao in Martinique - Claude, Jean-Philippe; Abati, Yelji; Jean-François, Yanis (Acta Geographica Debrecina Landscape & Environment series, 2026)
The current cocoa orchards in Martinique are genetically diversified and enjoy a good health situation. The aromatic properties of chocolates produced from Martinique beans seem exceptional. The cultivation of cocoa on this French island located in the Caribbean achieved international fame in the 18th century. Today, almost fifty farmers continue to grow cocoa, but climate projections indicate that the possibilities for growing this species will have considerably decreased in the coming decades. A geographic information system (GIS) was in fact developed using QGIS software version 3.36.2, to carry out an agroclimatic zoning and show the effect of climatic constraints on the distribution of environments suitable for Theobroma cacao, in Martinique. The climatic requirements of the species were defined based on global scientific literature and the environmental data comes from the French national meteorological services. Agroforestry, agro-ecology, plant selection and scientific innovations in agronomy will be the main ramparts to prevent a possible decline of this culture on the island.